PENGARUH SOSIALISASI TERHADAP EFEKTIVITAS PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM) DI KOTA GORONTALO - mattoasi mattoasi; Usman Usman; Didiet Pratama Musue (Jurnal Akuntansi dan Keuangan, 2021)
This study aims to see the effect of socialization on the enforcement of SAK Entities, micro, small and medium enterprises (EMKM) in Gorontalo Province. This research uses quantitative research methods. Sources of data used in this study are primary data obtained from questionnaires distributed to 99 respondents who are Entities micro, small and medium enterprises in Gorontalo Provinsi. Based on the result of the study, it shows that socialization has an effect on the effectiveness of the application of financial accounting standards for micro, small and medium enterprises by 13.9%, while the remaining 86.1% is explained by other variables not examined in this study.